Avaliação do efeito cicatrizante de Euphorbia tirucalli - SAUAIA FILHO, Euler Nicolau (2018)
Introduction: The use of plants in the prevention and treatment of diseases is an ancient practice. Aveloz (euphorbia tirucalli) is a plant native to Africa, widely distributed in tropical countries, Africa and Asia. The vegetable exudes in large quantity a white, acrid and caustic latex used as emetic and anti-syphilitic, being generally used among the natives of India as a purgative and, when applied externally for the treatment of rheumatism, neuralgia, warts. In addition to such activities, it also serves as anti-bacterial, molucicidal, anti-herpetic and anti-mutagenic. Objective: To evaluate the healing effect of euphorbia tirucalli. Methods: Ninety male rats (Rattus novergicus albinus, Rodentia mammalia) weighing between 140 and 200g were used. The animals were randomly assigned to 6 groups of 15 rats. The first will be called rupo Aveloz Bruto (GAB), Grupo Aveloz Metanólico (GAM) Grupo Aveloz Aquoso (GAA) Grupo Aveloz Hexanico (GAH) Grupo Aveloz Clorofórmio (GAC) e o Grupo Controle (GC). The groups were divided into 3 subgroups of 5 animals so-called: subgroup 3, 7 and 14 according to the days of death (3, 7 and 14 days. Animals in each group will be treated with solution of isolated compound from the corresponding group. The animals of each group were treated with solution of compound isolated from the corresponding group. The diameter of the lesion was evaluated daily and a histopathological study was carried out. Results: In the macroscopic analysis, there was a statistically significant difference in the GAA in the 14th DPO. There was better healing in GAA and GAB in relation to GC, as the presence of polymorphonuclear cells, mononuclear cells and collagen fibers in the 7th DPO; GAA presented a higher prevalence of mature collagen in relation to the other groups. Conclusion: Under the present study conditions, the crude extract of euphorbia tirucalli and the aqueous fraction caused an acceleration in the healing process of the injured skin of the 14-day postoperative subgroups.